Development and validation of a Brazilian nomogram to assess sentinel node biopsy positivity in melanoma. Issue 5 (October 2021) - Bertolli, Eduardo; Calsavara, Vinicius F.; de Macedo, Mariana P.; Pinto, Clovis A.L.; Duprat Neto, João P.
Background: Although well-established, sentinel node biopsy (SNB) for melanoma is not free from controversies and sometimes it can be questionable if SNB should be considered even for patients who meet the criteria for the procedure. Mathematical tools such as nomograms can be helpful and give more precise answers for both clinicians and patients. We present a nomogram for SNB positivity that has been internally validated. Methods: Retrospective analysis of patients who underwent SNB from 2000 to 2015 in a single institution. Single logistic regressions were used to identify variables that were associated to SNB positivity. All variables with a p value < 0.05 were included in the final model. Overall performance, calibration, and discriminatory power of the final multiple logistic regression model were all assessed. Internal validation of the multiple logistic regression model was performed via bootstrap analysis based on 1000 replications. Results: Site of primary lesion, Breslow thickness, mitotic rate, histologic regression, lymphatic invasion, and Clark level were statistically related to SNB positivity. After internal validation, a good performance was observed as well as an adequate power of discrimination (area under the curve 0.751). Conclusions: We have presented a nomogram that can be helpful and easily used in daily practice for assessing SNB positivity.